Spatial Modeling of Groundwater Quality Parameters on Mosul's Left Bank - Mohammed Khattab; Hazim Mahmood; Eman Al-Sarraj (Iraqi Geological Journal, 2023)
Spatial distribution of groundwater quality is one of the issues that are urgently requested from both the people and decision-makers, especially during the deficiency of water network supply. This work included creating spatial groundwater quality maps on Mosul's left bank. The water quality studied parameters were pH, EC, TDS, Ca2+, Mg2+, K+, Na+, SO42-, HCO3-, NO3-, Cl- and other chemical water quality parameters as well as heterotrophic bacteria. A statistical investigation has been done to evaluate the relationship between these parameters. An inverse distance weighted interpolation model was used to give these parameters a better geographical distribution pattern. The visual groundwater quality models gave an overview of this water source's environmental reality and possible pollution points. The results of this work could be employed as an effective tool in the field of planning and environmental protection of water resources in Mosul City because there is polluted groundwater on the eastern side of Mosul which is polluted by septic tanks and the sewage system